PENYULUHAN DAN PELATIHAN CTPS PADA ANAK USIA 4-12 TAHUN DI LAWEYAN SURAKARTA - Frahestina Frahestina; Nur Aini Azhari Nugrahani; Millah Kamilah; Qisty Dzakiyyatu Husna; Muhammad Naufal Mizan Auladi; Bethari Mukti Kusumaningtyas; Dewi Kurniawati; Rezania Asyfiradayati (LPPM Universitas Bina Bangsa, 2023)
Children's health is impacted by the practice of washing their hands. Parental efforts to teach kids to wash their hands with soap before eating have not been as effective as they may have been. Washing hands with soap and running water, often known as Washing Hands with Soap (Cuci Tangan Pakai Sabun, in Indonesian), is one of the indications of PHBS (Clean and Healthy Behavior). The lecture technique, question and answer, and demonstration of hand washing methods were used in this activity. The average posttest score of 74.47, compared to the average pretest score of 41.48, shows that there has been an improvement in understanding on how to perform handwashing with soap (CTPS) effectively and correctly. Later on, it is envisaged that it would be possible to improve health status and health quality